Nutritional counseling as a nutrition strategy in palliative care - Moura, Raquel Bezerra Barbosa de; Feitosa, Gina Araújo Martins; Olinto, Edcleide Oliveira dos Santos; Araújo, Pollyana Paula Almeida de; Cavalcanti, Isabel Carolina Pinto; Cavalcanti, Débora Silva; Araújo, Renan Gondim; Lacerda, Aline Honor; Cabral, Caroline Sousa; Barroso, Flávia Nunes de Lima (Seven Editora, 2023)
Palliative care is an approach that aims to alleviate suffering and improve the quality of life of patients facing a life-threatening illness, as well as their families and/or caregivers. The nutritionist is an important member of the multidisciplinary team who must act observing the pillars of palliative care, using strategies that seek to relieve symptoms related to food, as well as seeking to nourish the patient in line with their physical, psychological, religious and social aspects. Nutritional counseling is the first nutritional intervention strategy used by nutritionists. Regarding symptom management, this intervention had positive effects on a greater number of symptoms, namely: digestive symptoms, fatigue, dyspnea, inappetence, caloric-protein intake, anorexia, nausea/vomiting, xerostomia, and dysgeusia. Regarding quality of life, early and intensive nutritional counseling, in addition to the use of oral nutritional supplementation, offered positive results in cancer patients receiving radiotherapy, as well as in cancer patients in physical, emotional and social functioning scores. Several studies have also shown that nutritional counseling and the use of oral nutritional supplements, when indicated, lead to improvements in the nutritional status of patients in palliative care. Nutritional counseling is a fundamental step to facilitate nutritional therapy, including strategies that converge expertise and theoretical knowledge and considering each person's feelings, experiences, beliefs, and attitudes. Therefore, it is necessary to establish a bond between the nutritionist and the patient, which will allow them to guide them to necessary changes and improve adherence to nutritional therapy. DOI:https://doi.org/10.56238/sevened2023.004-012